A new design of stirling engine for automotive application. (5th August 2014) - Caputo, C.; Naso, V.
The advantages and disadvantages of the Stirling engine vis a vis conventional engines for automotive power are discussed. The paper describes a new Stirling engine design constructed by the authors, the essential feature of which is two interlocking pistons moving at right angles. Details of the mechanical arrangement and functioning are given. Tests are in progress to determine the efficacy of seals and balancing.